3(w-3)-9=-4(-5w+6)-7w

Simple and best practice solution for 3(w-3)-9=-4(-5w+6)-7w equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(w-3)-9=-4(-5w+6)-7w equation:


Simplifying
3(w + -3) + -9 = -4(-5w + 6) + -7w

Reorder the terms:
3(-3 + w) + -9 = -4(-5w + 6) + -7w
(-3 * 3 + w * 3) + -9 = -4(-5w + 6) + -7w
(-9 + 3w) + -9 = -4(-5w + 6) + -7w

Reorder the terms:
-9 + -9 + 3w = -4(-5w + 6) + -7w

Combine like terms: -9 + -9 = -18
-18 + 3w = -4(-5w + 6) + -7w

Reorder the terms:
-18 + 3w = -4(6 + -5w) + -7w
-18 + 3w = (6 * -4 + -5w * -4) + -7w
-18 + 3w = (-24 + 20w) + -7w

Combine like terms: 20w + -7w = 13w
-18 + 3w = -24 + 13w

Solving
-18 + 3w = -24 + 13w

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-13w' to each side of the equation.
-18 + 3w + -13w = -24 + 13w + -13w

Combine like terms: 3w + -13w = -10w
-18 + -10w = -24 + 13w + -13w

Combine like terms: 13w + -13w = 0
-18 + -10w = -24 + 0
-18 + -10w = -24

Add '18' to each side of the equation.
-18 + 18 + -10w = -24 + 18

Combine like terms: -18 + 18 = 0
0 + -10w = -24 + 18
-10w = -24 + 18

Combine like terms: -24 + 18 = -6
-10w = -6

Divide each side by '-10'.
w = 0.6

Simplifying
w = 0.6

See similar equations:

| 11.23(75.34-3x)=120.34 | | .5+3/5= | | 16.8a-v=6v | | 15.67-23.56=34.18x | | g=100-4t | | 0.25n-1.5=0.25n-1.5 | | -7(4x-7)=-80 | | P^2-20p+84=9 | | 111.78=67.8(2.7-4x) | | 4v-12-10=-5(v+9)-(v-6) | | 48+4x=-6+30-20x | | -11.0(x+3.33)=12.7 | | 3.7x+8=1.7x+9 | | 7x+1=-4-5 | | 7-6x=1-5x | | 4x^2+3xy-y^2=1 | | 33.8=7.6-2.06x | | 5b-4b=4b-2 | | 3t^2+22t+32=0 | | -17x-20-8x-2=128 | | 4(6-b)=12 | | 30-5x=16-3x | | 60-14x= | | -5+8x=-8x+23 | | 34x*2= | | x/7-23=48 | | 2(11+8n)=-26+12n | | a^2-10a+n=0 | | x+0.070=0.350 | | 2w(5w+3)=0 | | 2(x+2)3x=2(x+1)+1 | | 2[2(3-5x)+4]=5[2(3-3)+2] |

Equations solver categories